2021
DOI: 10.1177/00178969211061522
|View full text |Cite
|
Sign up to set email alerts
|

Improving infectious TB education for foreign-born patients and family members

Abstract: Objective: In low tuberculosis (TB) incidence countries, linguistic and cultural dissonance between families experiencing infectious TB and TB health care providers is a barrier to effective communication and successful treatment. The purpose of this research was to explore infectious TB education and counselling from the perspective of patients and family members who are foreign-born. Design/Setting: One component of a multiphase, qualitative case study conducted in Calgary, a large city in western Canada. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Herdianti et al ( 2020 ) emphasised that the family should be knowledgeable in TB prevention in order to take precautionary measures for themselves and their environment. Bedingfield et al ( 2022 ), in addition stated that the gaps in TB education and counselling have a negative impact on the patients and their families as they are meant to correct misconceptions about TB and reduce the transmission. In addition, Alberta and Widyastuti ( 2021 ), Sulistyono, Susanto and Tristiana ( 2020 ), found that personal TB protection was not practiced in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…Herdianti et al ( 2020 ) emphasised that the family should be knowledgeable in TB prevention in order to take precautionary measures for themselves and their environment. Bedingfield et al ( 2022 ), in addition stated that the gaps in TB education and counselling have a negative impact on the patients and their families as they are meant to correct misconceptions about TB and reduce the transmission. In addition, Alberta and Widyastuti ( 2021 ), Sulistyono, Susanto and Tristiana ( 2020 ), found that personal TB protection was not practiced in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia, it was reported that people who lived in households with only one room were five times more at risk of acquiring MDR-TB than those living in more than one room [ 24 ], which is coherent with the finding that there is a high risk related to acquiring resistant strains from infected hosts in crowded places. There is, therefore, the need for education on innovative and context-targeted strategies for persons with TB who may be sharing single rooms with their families and friends [ 25 ].…”
Section: Discussionmentioning
confidence: 99%